Effect of Vitamin D Supplementation on Overactive Bladder and Urinary Incontinence Symptoms in Older Men: Ancillary Findings From a Randomized Trial. Issue 1 (6th January 2023) - Markland, Alayne D.; Vaughan, Camille P.; Huang, Alison J.; Kim, Eunjung; Bubes, Vadim Y.; Tangpricha, Vin; Buring, Julie R.; Lee, I-Min; Cook, Nancy R.; Manson, JoAnn E.; Grodstein, Francine
Abstract : Purpose: Our goal was to evaluate vitamin D supplementation for preventing or treating overactive bladder and urinary incontinence in men. Materials and Methods: Ancillary study of men aged ≥55 years in VITAL (VITamin D and OmegA-3 TriaL). Randomized treatments included: vitamin D3 (cholecalciferol), marine omega-3 fatty acids, or matching placebo. Structured urinary incontinence questions measured the prevalence of overactive bladder at year 5 and urinary incontinence at years 2 and 5, along with incidence and progression of urinary incontinence from years 2 to 5. Prespecified subgroup analyses examined men with low baseline serum 25-hydroxyvitamin D (<20 ng/mL). Results: Among the 11, 486 men who provided data at year 2 and 10, 474 at year 5, mean age was 68 years at year 2, with 23% racial/ethnic minorities. In primary analyses, vitamin D supplementation compared to placebo did not lower odds of overactive bladder at year 5 (OR 0.97, 95% CI 0.87-1.08) or weekly urinary incontinence at year 2 (OR 0.94, 95% CI 0.83-1.05) or year 5 (OR 0.98, 95% CI 0.88-1.09). We found interactions of baseline serum 25-hydroxyvitamin D level with vitamin D supplementation for overactive bladder ( P value for interaction = .001), and secondarily, for any urinary incontinence at year 2 ( P value for interaction = .05). Men with baseline 25-hydroxyvitamin D <20 ng/mL, who were assigned to vitamin D supplements, had lower odds of overactive bladder (OR 0.51, 95% CI 0.35-0.76) compared to placebo, yet higher odds of any urinary incontinence (OR 1.24, 95% CI 0.93-1.64). Conclusions: Overall, vitamin D supplementation did not improve overactive bladder or urinary incontinence compared to placebo. However, specific use of vitamin D in men with lower 25-hydroxyvitamin D levels had inconsistent findings.